Recurrent unilateral vulval elephantiasis: a case report. - Lakshmidevi Muralidhar; Sampath Kumar G; Shreedhar Venkatesh (Journal of Family and Reproductive Health, 2014)
Genital elephantiasis is caused by a variety of infective and non infective causes leading to blockage of lymphatic. We are presenting a rare case of recurrent unilateral vulval elephantiasis which has recurred after initial reconstructive surgery. A 38 year old female presented with vulval swelling and on examination there was gross unilateral vulval enlargement. FNAC (Fine needle aspiration cytology) and biopsy were contributory for diagnosis. Patient was started with antibiotics and daily dressing was done till the infection was subsided and the patient was planned for reconstructive surgery.